Examining the Financial Development Channels Affecting Economic Growth in Turkey - Demirhan, Banu (Ekonomika, 2025)
In the early 1980s, Turkey took steps towards financial liberalization. Accordingly, policymakers have implemented policies for the development of the financial system. Since then, developments in the banking sector have driven economic growth and met the private sector’s demand for funds. The research problem involves analyzing the relationship between financial development and economic growth in Turkey, which is crucial in determining the effectiveness of policies implemented for financial development. Determining the source through which financial development is vital for economic growth is also critical in designing these policies. This research examines the channels through which financial development impacts economic growth in Turkey. By using data from 1974 to 2023 for Turkey, this study conducted a Granger causality test based on VECM and the Toda Yamamoto method to analyze the causal relationship between economic growth and financial development. The analysis also included impulse response functions. Our study reveals that financial development contributes to economic growth. Policymakers should implement policies that prioritize the development of the financial system.